Feasibility of a combined online and in-person training model on Infant and Young Child Feeding (IYCF) counselling for village health workers in rural Qinghai, China - Qiong Wu; Xinya Zhu; Tao Xu; Xiaotong Wang; Na Meng; Yanfeng Zhang; Suying Chang (PLoS ONE, 2025)
Background Counselling is an effective behavior change intervention for improving infant and young child feeding (IYCF). The Maternal and Health Department of National Health Commission China and United Nations Children’s Fund (UNICEF) China Office jointly developed a combined online and in-person IYCF counselling training course for primary health workers in rural China. This study aims to test feasibility of the combined training model in rural China. Methods The study was conducted between September 2021 and February 2022 in five counties in Qinghai Province, China. We implemented a “2+1” training model for village health workers in the five counties. This model consisted of a 2-day online training session followed by a 1-day in-person training session. After completing the training, each village health workers were requested to provide 12 IYCF counselling services to caregivers of children aged 6–23 months in their villages. We assessed the IYCF knowledge score of village health workers before and after online training, and collected satisfaction level of village health workers and caregivers by using a scale of 1–5. Values ≥4 were considered a high degree of satisfaction. Furthermore, we presented the per-person cost of the “2+1” training model. Results There were a total of 861 village health workers in the five counties, with 802 (93.1%) completed the 2-day online training course and 838 (97.3%) completed the 1-day in-person training course. The mean score of village health workers on IYCF knowledge significantly improved after 2-day online training (72.14 ± 17.84 before training vs. 82.00 ± 17.87 after training, P < 0.001), and their average satisfaction scores on the training were more than 4.5 for all items. Furthermore, more than 95% surveyed caregivers expressed satisfaction with the counselling services provided by village health workers, and around 80% caregivers reported that the counselling solved their feeding problems. The cost of “2+1” training model was ¥238.72 (US$33.38) per person. Conclusions This study showed that the combined online and in-person IYCF counselling training is acceptable and feasible with lower cost in rural of Qinghai, which can be scaled up in other rural areas in China.